Revisiting the Legacy of Hafshah bint Umar ibn al-Khattab: Towards a Model of Contemporary Muslimah Education - Mukminin, Moh. Amiril; Muzawwir, Ahmad; Sohib, Mubti; Mukit, Abdul; Zahiroh, Amni (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study aims to uncover the concept of Muslimah education as reflected in the life of Hafshah bint Umar ibn al-Khattab and to examine the relevance of her exemplary character as a role model for contemporary Muslim women. Amid increasingly complex challenges of the modern era, the exemplary conduct of women in Islamic history is urgently needed as a reference for character education. However, studies that systematically integrate classical Islamic female figures into modern Islamic educational frameworks remain limited. Therefore, a new approach is required to bring forward their legacy as a valuable foundation. This research adopts a qualitative descriptive method through library research, analyzing both classical and contemporary literature. The findings show that Hafshah RA was a prominent shahabiyah known for her love of knowledge, moral resilience, and her significant role in preserving the written Qur’an. Her contribution to hadith transmission and involvement in the social life of the Muslim community reflect her high level of integrity and intellectual capacity. Values such as courage, intelligence, steadfast faith, and social concern are examined in terms of their relevance to current Islamic character education curricula. The novelty of this study lies in its systematic effort to present Hafshah RA as a model of Muslim women’s character that can be integrated into contemporary Islamic education design an approach that has been rarely addressed in previous scholarship. This study concludes that integrating the exemplary legacy of Hafshah RA into character education is essential for shaping morally upright, critically minded, and independent Muslim women.